Innovations in collagen-network remodeling and extracellular matrix mechanics: toward a new era in articular cartilage repair - Huang, Kai; Hong, Yifan; Cai, Haili (Frontiers in Bioengineering and Biotechnology, 2026)
Articular cartilage is a highly specialized connective tissue with a hierarchically organized extracellular matrix (ECM) that provides the mechanical resilience necessary for joint function. Central to this functionality is the depth-dependent architecture of collagen—primarily type II—interwoven with proteoglycans, enabling efficient resistance to compressive and shear stresses. This review synthesizes recent advances in ECM dynamics, emphasizing the interplay between collagen organization, viscoelastic microenvironments, and pericellular-matrix (PCM)–mediated mechanotransduction. Emerging evidence implicates type III collagen as a regulator of early cartilage remodeling and a putative biomarker of osteoarthritis (OA) progression. Additionally, we highlight cutting-edge studies on the synergistic effects of mechanical loading and enzymatic degradation on collagen integrity, providing novel insights into ECM deterioration in disease contexts. We evaluate next-generation biomaterials—including viscoelastic hydrogels, anisotropic scaffolds, and magnetic field–assisted fiber alignment—designed to recapitulate the native anisotropy and multiscale mechanics of cartilage. Together, these recent developments redefine the landscape of cartilage repair and delineate promising avenues for translational regenerative therapies.